Mental Health Literacy Training for Surabaya Hebat Cadres to Improve Psychological Wellbeing of the Elderly - Qurrotu Ainin; Dian Kartika Amelia Arbi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The program aims to improve the welfare of the elderly and prevent the elderly from experiencing mental health problems through mental health literacy training to elderly posyandu cadres to help and assist the elderly to detect psychological disorders so that the elderly can immediately seek help to get the right treatment independently or through professional assistance. This study used an experimental approach with a one-group pretest posttest design. The research subjects were Surabaya Hebat cadres who were also members of the Karang Werdha Amanah RW 07 Pucang Sewu Surabaya elderly community, totaling 12 people. The results of cognitive mental health literacy questionnaire analysis using paired sample t analysis through the SPSS 25 application showed a significance value of 0.009 (p